Do Environmentally Responsible Practices in Accommodation Establishments Matter? - NDZUNGU, Lulama; KLEYNHANS, Carina; ROELOFFZE, Antoinette (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).09, 2023)
Environmentally responsible practices (ERPs) in accommodation establishments are identified as the implementation and or execution of certain principles in such a way that it lowers the production of waste, preserve energy, and encourages environmental health. The main purpose of this study is to identify whether or not environmentally responsible practices in accommodation establishments matters. A descriptive survey design was used. The study utilised a quantitative research approach with questionnaires as a data collection instrument. The data were analysed using Statistic Package for the Social Science (SPSS), software version 23, to enable the generation of descriptive and bivariate statistics for the interpretation of the results. The following themes emerged from the study; namely, guests’ preferences of ERPs, influence of return patronage and the effect knowledge have on ERPs. Most participants were not bothered by the re-use of linen and towels, yet establishments still need to invest more time in educating the guests in this regard. Guests indicated that they would return to an accommodation establishment that practices linen reuse programs, water conservation and waste management procedures. This study provides insights on ways guests view ERPs and their preferences. It provides accommodation establishments a scope on what their guests are comfortable in participating on.